Resolution-Enhanced Ptychographic Modulation Imaging via Divergent Illumination - Jun Lan; Cheng Xu; Hui Pang; Song Hu; Yong Yang (IEEE Photonics Journal, 2024)
By inserting a modulator in the imaging system and scanning in different positions, ptychographic modulation imaging can achieve higher quality reconstruction for smooth or weakly scattered objects compared to conventional ptychography imaging. However, its imaging resolution is still limited by the pixel size of the detector. In this paper, divergent illumination is introduced to enhance imaging resolution. Compared with the original planar illumination scheme, our proposed method can achieve two-fold resolution improvement with only the use of thirty diffraction patterns for ten iterations. The quantitative phase imaging capability of the proposed method is also demonstrated by testing the binary phase sample. In the reconstruction, the divergent illumination geometry is converted to planar illumination model. The equivalent sampling intervals and diffraction distances of the modulator, object, and detector planes are analyzed in detail. In addition, a new high-accuracy distance calibration method for point light sources is proposed and verified in experiments.